Recent Advances in Traffic Engineering for Transport Networks and Systems 14th Scientific and Technical Conference "Transport Systems. Theory & Practice 2017" Selected Papers - Macioszek, Elżbieta; Sierpiński, Grzegorz (Lecture Notes in Networks and Systems,, 2018)
This book is a collation of numerous valuable guidelines for making decisions based on recent advances and improvement of transport systems. Offering know-how and discussing practical examples as well as decision-making support systems it is of interest of those who face the challenge of seeking solutions to contemporary transport system problems on a daily basis, including local authorities involved in planning and preparation of development strategies for specific transport related areas (in both urban and regional dimension) as well as representatives of business and industry who participate directly in the implementation of traffic engineering solutions. The guidelines are provided in individual chapters, making it possible to address the given problem in an advanced manner and simplify the choice of appropriate strategies (including those related to increasing competitiveness of public transport; identifying bus lines to potentially be serviced by electric buses; pedestrian traffic solutions; developing bike-sharing systems; safety conditions in road tunnels; integrating supply chains or route planning support by means of technologically advanced systems and applications). On the other hand, since the book also addresses the new approach to theoretical models (including traffic flow surveys and measurements, transport behaviours, capacity models, delay modelling and road condition modelling), it appeals to researchers and scientists studying this body of problems. The book entitled Recent Advances in Traffic Engineering for Transport Networks and Systems includes selected papers submitted to and presented at the 14th Scientific and Technical Conference "Transport Systems. Theory and Practice" organised by the Department of Transport Systems and Traffic Engineering at the Faculty of Transport of the Silesian University of Technology. The conference was held on 18-20 September 2017 in Katowice (Poland). .